Peran Pendidikan Islam Dalam Menanggulangi Radikalisme Agama - Bustanur Bustanur; Alhairi Alhairi (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
This study discusses the role of Islamic religious education in tackling religious radicalism with the aim of looking at the role of Islamic education in tackling religious radicalism. This study aims to determine the role of Islamic religious education in tackling religious radicalism. This study uses a qualitative research type by using content analysis, namely:research that is an in-depth discussion of the content of written or printed information in various references that examines the issue of religious radicalism.From the results of the analysis carried outnamely Islamic education which includes family and community schoolscarry out the right learning process by instilling the value of love and friendship, then the regeneration of radicals will be amputated so that terror does not happen again on this earth